Curcumin attenuates cardiomyocyte hypertrophy induced by high glucose and insulin via the PPARγ/Akt/NO signaling pathway. Issue 2 (May 2015) - Chen, Rongchun; Peng, Xiaofeng; Du, Weimin; Wu, Yang; Huang, Bo; Xue, Lai; Wu, Qin; Qiu, Hongmei; Jiang, Qingsong
Highlights: The mechanism of diabetic cardiomyopathy is still unclear. We made an in vitro diabetic cardiac hypertrophy model with HGI. We found PPARg/Akt/NO signal pathway was involved in diabetic cardiac hypertrophy. Curcumin attenuates cardiac hypertrophy induced by HGI via this pathway. Abstract: Aim: To investigate the potential effect of curcumin on cardiomyocyte hypertrophy and a possible mechanism involving the PPARγ/Akt/NO signaling pathway in diabetes. Methods: The cardiomyocyte hypertrophy induced by high glucose (25.5 mmol/L) and insulin (0.1 μmol/L) (HGI) and the antihypertrophic effect of curcumin were evaluated in primary culture by measuring the cell surface area, protein content and atrial natriuretic factor (ANF) mRNA expression. The mRNA and protein expressions were assayed by reverse transcription PCR and Western blotting, whereas the NO concentration and endothelial NO synthase (eNOS) activity were determined using nitrate reduction and ELISA methods, respectively. Results: The cardiomyocyte hypertrophy induced by HGI was characterized by increasing ANF mRNA expression, total protein content, and cell surface area, with downregulated mRNA and protein expressions of both PPARγ and Akt, which paralleled the declining eNOS mRNA expression, eNOS content, and NO concentration. The effects of HGI were inhibited by curcumin (1, 3, 10 μmol/L) in a concentration-dependent manner. GW9662 (10 μmol/L), a selective PPARγ antagonist, could abolish the effects of curcumin. LY294002 (20 μmol/L), an Akt blocker, and N G -nitro-l -arginine-methyl ester (100 μmol/L), a NOS inhibitor, could also diminish the effects of curcumin. Conclusions: The results suggested that curcumin supplementation can improve HGI-induced cardiomyocytes hypertrophy in vitro through the activation of PPARγ/Akt/NO signaling pathway.